Aceitação e intenção de compra do queijo tipo coalho de búfala e de vaca no município de Areia - PB - Vasconcelos, Gisele Maria Alves dos Santos (2016)
The base products of bubalino milk and beef, especially the cheeses, great sensory and nutritional quality feature. The objective of this work to determine the degree of acceptance and purchase intent of rennet cheese bubalino in comparison to bovine rennet cheese by the population of the municipality of Areia-PB. 112 untrained judges participated, with ages ranging between 18 and 60 years, of both sexes. People were covered in a supermarket in the city, and also at the Federal University of Paraíba, Campus II, offered to testers two samples of cheese curds into cubes approximately 2 cm ², accompanied by mineral water and cracked water and salt. In the beginning was offered sample CSF, water and crackers and salt water to clear the palate of the dressing room and then the sample QCB. The taster evaluated samples and tagged as their affection for the product offered, scoring points in a seven-point hedonic scale, ranging from "I really liked the disliked a lot" and the test of intention to purchase. Averages were calculated and then the percentages of each response. The CSF product (cheese curds), obtained greater acceptance, corresponding to 69.64%, while QCB (Bubalino cheese curds) 32.14% only. The CSF product reached a percentage of 98.21% and QCB obtained 77.68% acceptance scale, ranging from "" to "very slightly", both results are taken as acceptance of the products. The average score for the CSF was 6.6 ranging from liked moderately and enjoyed, since the QCB average score 5.5 presented, ranging from slightly liked and I liked it moderately. Both results are positive, although there is still a certain cultural influence in the daily life of the people who affect your taste buds. Nevertheless the purchase intent results showed, that the CSF has obtained the highest percentage of purchase intent (89.29%) while the QCB reached 47.32%. However 30.36% of evaluators possibly buy the product QCB. Yet the results showed that there is a positive acceptance to bubalino rennet cheese, for being considered by tasters more nutritious and healthy.